Treatment Practices for Adults With Candidemia at 9 Active Surveillance Sites—United States, 2017–2018. (3rd June 2021) - Gold, Jeremy A W; Seagle, Emma E; Nadle, Joelle; Barter, Devra M; Czaja, Christopher A; Johnston, Helen; Farley, Monica M; Thomas, Stepy; Harrison, Lee H; Fischer, Jill; Pattee, Brittany; Mody, Rajal K; et al.
Abstract: Background: Candidemia is a common opportunistic infection causing substantial morbidity and mortality. Because of an increasing proportion of non- albicans Candida species and rising antifungal drug resistance, the Infectious Diseases Society of America (IDSA) changed treatment guidelines in 2016 to recommend echinocandins over fluconazole as first-line treatment for adults with candidemia. We describe candidemia treatment practices and adherence to the updated guidelines. Methods: During 2017–2018, the Emerging Infections Program conducted active population-based candidemia surveillance at 9 US sites using a standardized case definition. We assessed factors associated with initial antifungal treatment for the first candidemia case among adults using multivariable logistic regression models. To identify instances of potentially inappropriate treatment, we compared the first antifungal drug received with species and antifungal susceptibility testing (AFST) results from initial blood cultures. Results: Among 1835 patients who received antifungal treatment, 1258 (68.6%) received an echinocandin and 543 (29.6%) received fluconazole as initial treatment. Cirrhosis (adjusted odds ratio = 2.06; 95% confidence interval, 1.29–3.29) was the only underlying medical condition significantly associated with initial receipt of an echinocandin (versus fluconazole). More than one-half (n = 304, 56.0%) of patients initially treated with fluconazole grew a non- albicans species. Among 265 patients initially treated with fluconazole and with fluconazole AFST results, 28 (10.6%) had a fluconazole-resistant isolate. Conclusions: A substantial proportion of patients with candidemia were initially treated with fluconazole, resulting in potentially inappropriate treatment for those involving non- albicans or fluconazole-resistant species. Reasons for nonadherence to IDSA guidelines should be evaluated, and clinician education is needed. Abstract : We analyzed US population-based candidemia surveillance data to describe adherence to Infectious Diseases Society of America guidelines, which recommend echinocandins over fluconazole as first-line treatment for adults. More than 25% of candidemia patients initially received fluconazole, resulting in potentially inappropriate treatment.